Strategy for Accelerating Business Unit Optimization and Financial Independence of I Gusti Bagus Sugriwa Denpasar State Hindu University Towards a Public Service Agency - I Nengah Wirawan Kawiguna (POKJANAS PERENCANA KEMENTERIAN AGAMA RI, 2026)
This policy paper discusses the transformation of I Gusti Bagus Sugriwa State Hindu University (UHN) Denpasar into a Public Service Agency (BLU) hampered by the limited number and type of business units, which has implications for the inability to achieve the targets of financial independence and asset optimization as the main prerequisites of BLU. This policy analysis finds that the main root of the problem lies in the weakness of internal regulations that support asset commercialization, as well as the limited understanding of cost recovery and business-like principles at the policy-making level. This policy analysis framework uses a descriptive-prescriptive writing method, supported by the theoretical framework of New Public Management (NPM), Vroom's Expectancy Theory, and the Entrepreneurial University Concept, and is tested using William N. Dunn's policy alternative scoring tool to determine solution priorities. The scoring results determine the policy alternatives as the highest priority: Regulation of Asset Commercialization and Determination of Business-like Tariffs. The main policy recommendation is to immediately issue a Rector's Regulation that provides a legal umbrella for the utilization of idle assets and ensures service pricing based on cost recovery plus margin, thereby enabling UHN I Gusti Bagus Sugriwa to achieve financial flexibility and operational readiness of BLU effectively.